Detection of feline immunodeficiency provirus by seminested polymerase chain reaction - Celer, V; Kulhánková, H; Celer, V (Folia microbiologica, 2000)
Specific primers for the detection of the FIV provirus in peripheral blood mononuclear cells (PBMC) by seminested PCR (snPCR) were developed. Forty cats (patients from veterinary hospitals) were investigated for the presence of FIV serum antibodies by immunoblot and for the presence of provirus in PBMC by snPCR. Seventeen of the 40 examined samples (42.5%) showed the presence of antibodies against FIV. The total number of animals that were found positive in snPCR was 19 (47.5%). Fourteen of the seropositive animals (35%) were positive by snPCR whereas three seropositive animals (7.5%) turned out to be snPCR negative. Of twenty-three animals that were negative by immunoblot, five (12.5%) were found to be positive by snPCR.
Keywords: imunoblotting; Sensitivity and Specificity; senzitivita a specificita; kočky; lentivirové infekce; Leukocytes, Mononuclear; zvířata; Cat Diseases; nemoci koček; virus kočičí imunodeficience; proviry; DNA virů; polymerázová řetězová reakce; DNA, Viral; Polymerase Chain Reaction; protilátky virové; leukocyty mononukleární; Immunoblotting; Antibodies, Viral; Cats; Animals; Immunodeficiency Virus, Feline; Proviruses; Lentivirus Infections